Effect of varying design options on the transient behavior of a hybrid rocket motor - Kafafy, Raed Ismail; Azami, Muhammad Hanafi; Idres, Moumen (Instituto de Aeronautica e Espaco-IAE, 2014)
Hybrid rockets provide compelling features for use in atmospheric and space rocket propulsion. One of the prominent applications of hybrid rockets which foster on its characteristics is the propulsion of micro air launch vehicles. In this paper, a set of design options of a hybrid rocket motor is evaluated for propulsion of micro air launch vehicles. In order to evaluate the various design options of a hybrid rocket, we developed design and performance simulation codes. A simulation code is based on a legacy interior ballistic model. MATLAB® environment was used to develop the design and performance analysis codes and to visualize the temporal variation of performance characteristics and grain geometry during burning. We employ the developed codes to assess the replacement of solid rocket motors which are typically used in Air Launch Vehicles by hybrid rocket motors. A typical Micro Air Launch Vehicle mission to launch a 20-kg payload into a 400-km circular polar orbit is assumed. The results show that a hybrid rocket is a suitable candidate for micro air launch vehicles. The performance is improved in terms of specific impulse and thrust with smaller size in the same mission. Several design parameters of hybrid rocket motors were also evaluated and analyzed, including different fuel port geometry, type of fuels and oxidizers, number of ports, nozzle design and initial mass flux. These design parameters bring a significant effect on hybrid rocket performance and size.